Here Lies the Librarian - Peck, Richard (New York Dial Books, 2006)
Fourteen-year-old Eleanor "Peewee" McGrath, a tomboy and an automobile enthusiast, discovers new possibilities for her future after the 1914 arrival in her small Indiana town of four young librarians.
Elementary
Keywords: Automobiles - Fiction; Automobile racing - Fiction; Librarians - Fiction; Indiana - History - 20th century - Fiction